Perivascular adipose tissue in the pathogenesis of cardiovascular disease - O. T. Kim; V. A. Dadaeva; A. I. Korolev; O. M. Drapkina (Российский кардиологический журнал, 2021)
Perivascular adipose tissue (PVAT) is an active regulator of vascular homeostasis. In physiological conditions, it maintains normal function of vessels, releasing antiatherogenic, anti-inflammatory and vasodilating biologically active substances. Dysfunctional PVAT secretes pro-inflammatory cytokines and adipokines, which play an important role in the development of cardiovascular diseases. This review considers the PVAT function in health and disease, its contribution to the pathogenesis of atherosclerosis, hypertension, aortic aneurysm and vasculitis. In addition, novel methods of non-invasive PVAT assessment and potential strategies for targeted treatment of cardiovascular diseases are presented.